A participa????o pol??tica do surdo: h?? poder em suas m??os - Collado, Maria Laide dos Santos (2016)
The present work is a qualitative research using bibliographical nature and sources of the field research to answer the following questions: how the deaf community participates in the construction of public policies for education of the deaf population of school age? What deaf people say about their participation in policy decisions? Who do they represent? It is understood that the history of deaf education is marked by the laying on of the model about the deaf listener: listeners decided that the oral method in the education of the deaf should be privileged to the detriment of sign language; listeners thought they are able to govern life and denied the deafs the right to be a citizen to participate in political decisions. They followed the view that deafness was a disease that needed to be treated. However, the deaf have formed groups of resistance to oppression exerted by listeners and promoted the strengthening of deaf culture through the recognition of sign language. Today, a new concept has formed about deafness, a social anthropological conception which considers deafness as a possibility of being different and recognizes the deaf as political, historical subject, with linguistic difference and with own culture. Nowadays, the deaf community recognizes its power, the political issues and has occupied several academic spaces. This study has as its main theoretical, Antonio Gramsci. For his contribution to analytical categories help in understanding the performance of the deaf as intellectually and militants today; the importance of the deaf associations as institutions where organic intellectuals act and especially the importance of education policy that raises the level of "masses" by the consciousness of its historical contradictions and rights. This research had as field locus the first ???Date of Deaf??? (Encontro de Surdas e Surdos) in Goiania. This event has contributed to the understanding of the activities and political engagement of the deaf.